Psychological Well-Being of Patients with Breast Cancer: A Descriptive Study - Widyaningsih, S.; Istifaraswati, A. (Sainteks, 2020)
The mental impact of cancer on patients is often severe. Patients who have been recently diagnosed with breast cancer tend to experience depression, emotional stress, disappointment, and even despair which later can damage their psychological well-being. This study aims to describe Psychological Well-being among breast cancer patients.134 breast cancer patients were recruited at the Out Patient Department (OPD) of Tugurejo Hospital Semarang city, Indonesia. The data were collected using Ryff Scale Psychological Well-being (RSPWB) questionnaire. Most of the respondents were middle-aged, married, unemployed and had been diagnosed with early stadium of breast cancer. Results showed approximately half of the total respondents (n=64%, 47.8%) experiencing low levels of psychological well-being over the entire period of the sickness. Among four subscales of psychological well-being, “positive relationship with others” subscale was reported to be very low among those respondents. However, almost two thirds of respondents perceived a higher degree of self-acceptance and life purpose while experiencing the illness. Nurses and healthcare providers need to be aware of the importance of counseling service and family/patients support group to improve the relationship of patients with others. Keywords: psychological well-being, breast cancer